Privilege and Discipline: An Exploration into the Role of Social and Cultural Capital in Cape Town ex-Model C Schools - Arlt, Felix Julius (Department of Public Law, 2024)
This dissertation examines the disciplinary practices in ex-Model C schools, situated in affluent, white areas under apartheid, in Cape Town, South Africa, focusing on their disciplinary principles and the management of disciplinary processes. The research, grounded in theories of social control, labelling, and social capital, sought to uncover factors driving disciplinary actions and their outcomes specifically in these settings. Typically serving a higher socio economic student demographic, these schools are recognised for their exceptional education and discipline standards. In contrast to prior South African research that often highlights the negative aspects of school discipline, this study explores the components of an effective and non-detrimental disciplinary system, as well as the contributions of various participants to this system. Through interviews with heads of discipline and other staff, the research finds characteristics of these schools that support progressive and inclusive disciplinary approaches. It finds a notably low occurrence of serious infractions, which can be attributed to a robust community that results in substantial social control. The study reveals that the disciplinary process in these schools is characterised by a synergistic relationship among schools, parents, and students, leading to the effective deployment of specific social and cultural capital. Overall, this dissertation not only reaffirms existing literature but also deepens the understanding of the elements that constitute a positive disciplinary culture and underscores the central role of parental collaboration in addressing issues of indiscipline.